Influence of Board Characteristics on Financial Performance of Deposit Taking Savings and Credit Cooperative Societies in Western Kenya (Global Journal of Management and Business Research, 2021)
Deposit taking Savings and Credit Cooperatives form an integral part of Kenya's economy by mobilizing savings and promoting credit creation. Statistics indicate that DT-Saccos contribute up to 23% to Kenya's GDP, both directly and indirectly. However, the performance of a number of these DT-SACCOs in the western part of Kenya have shown to be reporting reduced profits indicating challenges with their financial performance. Prior studies on the performance of these SACCOs have not focused on the role of board characteristic on financial performance of these SACCOs. The purpose of this research was to examine influence of board characteristics on financial performance of deposit taking SACCOs in the country. Specifically, this study examined board accountability, corporate size and board independence and how they affect the performance. The study was anchored on the Agency theory and the Stakeholder theory. The study adopted a descriptive survey design to address the research problem. The target population consisted of 19 deposit taking Saccos licensed Saccos by SASRA and operating in Western Kenya.